The effect of mobile phone task and age on gait: A systematic review and meta-analysis - Zhang, Xinxin; Li, Qiang; Gao, Pincao; Zhu, Jialin; Tuo, Haowen; Lin, Qihan; Jing, Feiyue; Liu, Weiguo (Frontiers in Physiology, 2023)
Objective: Mobile phone usage while performing postural-locomotor tasks is everyday activity across persons of all ages in various environmental contexts and health conditions. However, it is also an important factor contributing to accidents. To lower the risk of pedestrian accidents, this meta-analysis aimed to examine how mobile phones affect pedestrian gait and identify how mobile phone tasks and participant age affect gait differently. Methods: Electronic database searches were performed in The Cochrane Library, PubMed, and Medline. Two examiners evaluated the eligibility and quality of included studies using the Downs and Black checklist. The mean differences (MD) or standardized mean differences (SMD) were calculated for each outcome. Subgroup analyses were used to compare the differential effects of mobile phone task and participant age on gait. Results: Among 22 eligible studies, 592 participants in 10 countries were analyzed in this meta-analysis. The overall meta-analysis showed that using a mobile phone significantly decreased pedestrian gait velocity (SMD=-1.45; 95% CI: -1.66 to -1.24; p<0.00001; I2=66%), step length (SMD=-1.01; 95% CI: -1.43 to -0.59; p<0.00001; I2=82%), and stride length (SMD=-0.9; 95% CI: -1.19 to -0.60; p<0.00001; I2=79%), significantly increased pedestrian step time (SMD=0.77; 95% CI: 0.45 to 1.08; p<0.00001; I2=78%), stride time (SMD=0.87; 95% CI: 0.69 to 1.06; p<0.00001; I2=24%), step width (SMD=0.79; 95% CI: 0.34 to 1.24; p=0.0006. I2=75%), double support time (SMD=1.09; 95% CI: 0.86 to 1.31; p<0.00001; I2=42%), and double support (%gait cycle, %GC) (MD=2.32; 95% CI: 1.75 to 2.88; p<0.00001; I2=26%). Conclusion: In summary, the effects of mobile phone tasks and participant age on gait were inconsistent. Our study found that resource-intensive tasks (texting and reading) significantly reduced gait velocity, and step time; however, small resource-intensive tasks (calling, talking, and dialing) did not affect these outcomes. In contrast to young adults, step length and step time were not affected by mobile phone use in older adults. Tips: Pedestrians should consider using a mobile phone in their daily lives according to the application scenarios (walking environment, the complexity of mobile phone tasks, pedestrians' task processing abilities, etc.) as appropriate to avoid dangerous accidents.